Nucleotide sequence and genetic organization of the Bacillus subtilis comG operon. - Albano, M (1989)
A series of Tn917lac insertions define the comG region of the Bacillus subtilis chromosome. comG mutants are deficient in competence and specifically in the binding of exogenous DNA. The genes included in the comG region are first expressed during the transition from the exponential to the stationary growth phase. From nucleotide sequence information, it was concluded that the comG locus contains seven open reading frames (ORFs), several of which overlap at their termini. High-resolution S1 nuclease mapping and primer extension were used to identify the 5' terminus of the comG mRNA. The sequence upstream from the comG start site closely resembled the consensus recognition sequence for the major B. subtilis vegetative RNA polymerase holoenzyme. Complementation analysis confirmed that the comG ORF1 protein is required for the ability of competent cultures to resolve into two populations with different cell densities on Renografin (E. R. Squibb & Sons, Princeton, N.J.) gradients, as well as for full expression of comE, another late competence locus. The predicted comG ORF1 protein showed significant similarity to the virB ORF11 protein from Agrobacterium tumefaciens, which is probably involved in T-DNA transfer. The N-terminal sequences of comG ORF3 and, to a lesser extent, the comG ORF4 and ORF5 proteins were similar to a class of pilin proteins from members of the genera Bacteroides, Pseudomonas, Neisseria, and Moraxella. All of the comG proteins except comG ORF1 possessed hydrophobic domains that were potentially capable of spanning the bacterial membrane. It is likely that these proteins are membrane associated, and they may comprise part of the DNA transport machinery. When present in multiple copies, a DNA fragment carrying the comG promoter was capable of inhibiting the development of competence as well as the expression of several late com genes, suggesting a role for a transcriptional activator in the expression of those genes.